Exploring summer cooling electricity consumption in a mid-sized, semi-arid city - Abram, Lauren, author; McHale, Melissa, advisor; Keller, Joshua, committee member; Tulanowski, Elizabeth, committee member (Colorado State University. Libraries, 2021)
As climate change advances, it will threaten urban livability in the summer months through elevated temperatures and more severe heat waves. These increased temperatures, coupled with urbanization and the introduction of more impervious surfaces, will positively feed into the Urban Heat Island (UHI) effect. The combination of hotter temperatures and the inevitable population growth urban areas are going to experience will threaten sustainability through the increased demand for cooling energy resources. While there are many ways to address sustainable energy consumption in a city, one commonly cited method has been through the establishment of urban tree canopy (UTC), which has been shown to cool outdoor temperatures and decrease summer energy use through shading and microclimate regulation. Additionally, investing in research to understand local drivers of cooling energy use can help inform the development of municipal goals and programs for energy reduction. Using household electricity consumption, we aimed to understand if UTC and impervious surfaces were impacting summer cooling electricity use in single-family homes, and if so, at what distance and orientation around homes were these land covers most impactful. We then investigated drivers of summer cooling electricity use with additional urban form, building, sociodemographic, and behavioral variables to try to account for cooling consumption patterns. We found that our results showed trends that differed from previous studies and that east side UTC was the most impactful on cooling use. In addition, impervious surfaces were the most impactful when they were closer to the home. However, land cover was minimally impactful on cooling use, and additional behavioral, building, urban form, and sociodemographic characteristics explained more variability in cooling consumption patterns and highlighted the uniqueness of our study area in comparison to previous studies.
Keywords: energy savings; tree benefits; urban structure; residential; cooling energy; urban ecology